Topological structure of the space of composition operators on the Hardy space of Dirichlet series - Bayart, Frédéric; Wang, Maofa; Yao, Xingxing (Journal of functional analysis, 2025)
The aim of this paper is to study when two composition operators on the Hilbert space of Dirichlet series with square summable coefficients belong to the same component or when their difference is compact. As a corollary we show that if a linear combination of composition operators with polynomial symbols of degree at most 2 is compact, then each composition operator is compact.